Além da indexação: papel das hashtags na circulação do caso Valentina Schulz - Kastner, Gabriela Schuch (Universidade do Vale do Rio dos Sinos, 2018)
With the technological and behavioral evolutions through which we pass is going faster, it is fundamental to understand the consequences of the media field in this scenario. Therefore, the present research aims to understand how media logics are triggered by new mechanisms, affecting the process of production of meaning. Based on the Valentina Schulz case and the MasterchefBR and PrimeiroAssedio (FirstHarassment) hashtags, we seek to understand the role of the hashtag that, once affected by the mediatization processes (reinscriptions, visibilities), moves from indexer to an interactive reference device. In addition, the objective is to analyze how circulation movements - characteristic of a mediatized society - are shaped in the production of meaning of content and the importance of these meanings in the generation of new voices related to these new senses. Finally, we try to understand the role of the media in legitimizing themes. To do this, two movements are carried out: a case study on the peculiarities of what occurred with the girl Valentina and its repercussion in the network and the subsequent content analysis on the circulation of the case in order to identify the mediatization in macro and micro moments of the process and thus perceives it as fundamental in the whole process of producing meaning.
Keywords: Midiatização; Circulação; Produção de sentido; Hashtags; Masterchef Brasil; Primeiro assédio; Mediatization; Circulation; Hashtags; Masterchef Brazil; First harassment; ACCNPQ::Ciências Sociais Aplicadas::Comunicação